Subjective Transcendentalism, Contingency and Medicinal Plants - Webster, Duncan (DALHOUSIE MEDICAL JOURNAL, 2000)
This paper is based on a discussion with two traditional healers from the Mi'kmaaq reserve of Eskasoni in Cape Breton. Medicinal plants are at the centre of the discussion, however, on the circumference there were a variety of topics. The discussion was followed with a literature search, aspects of which have been incorporated into the body of the paper. A variety of physicians and health care workers were also of great value through ongoing dialogue. This paper is without a final conclusion, analogous to a circle that has no point but its own centre.